(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The investigation focused on examining of the survival analysis which entails the design and study of the occurrence and time of survival events. The study aimed to compare the result of the analysis using semi parametric model; cox mixed cure model and two parametric models; weibull and lognormal model to determine the model that fit the toxic data. The data was obtained from State Special Hospital Maiduguri (SSH) from 2016-2020. Akaike information criterion (AIC) was used to compare and evaluate the models. Results show that Cox mixed cure model has 13.65 with least AIC value, Weibull with 18.29 and lognormal with 18.30 with highest AIC value. The study concludes that semi parametric cox mixed cure model is the suitable to fit the toxic data.